2010
DOI: 10.1007/s11671-010-9565-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Thiol-Stabilized Gold Nanoparticles by Heat-Induced Coalescence

Abstract: A monolayer of dodecanethiol-stabilized gold nanoparticles changed into two-dimensional and three-dimensional self-organized structures by annealing at 323 K. Subsequent crystal growth of gold nanoparticles occurred. Thiol molecules, although chemisorbed, form relatively unstable bonds with the gold surface; a few thiols desorbed from the surface and oxidized to disulfides at 323 K, because the interaction energy between thiol macromolecules is larger than that between a thiol and a nanoparticle. The gold nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…A second key point for the development of contacts could be the surface mobility of gold atoms, which might partially cause a reorganization of the domains after linking (which however we are unable to exclude) ,…”
Section: Resultsmentioning
confidence: 94%
“…A second key point for the development of contacts could be the surface mobility of gold atoms, which might partially cause a reorganization of the domains after linking (which however we are unable to exclude) ,…”
Section: Resultsmentioning
confidence: 94%
“…2,3 Sintering process of nanoparticles represents an interesting and important topic in evaluating stability of colloidal nanoparticles, and the corresponding knowledge can help us develop methods to prevent sintering and thus improve stability of the nanoparticles. [9][10][11][12][13] The sublimation of Ag nanoparticles with size over 20 nm was investigated by in-situ TEM under elevated temperatures, indicating the dependence on facets. The electron beam dose effects on sintering of passivated Au nanoparticles driven by surface atom diffusion rather than Ostwald ripening.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM image in Fig 5 , taken at 50k x and 65k x magnification, shows the detailed inner structure of GNRDS aggregates formed upon evaporative self-assembly and the thermal process in the presence of the removable silicon support. It has been previously reported that thermal treatment of thiol-capped GNRDs can lead to coalescence of the GNRDs in ordered aggregates [ 70 ] as the thiol-alkyl chains behave more as a liquid than a solid. [ 71 ] Therefore, we propose that under such conditions the thiol-capped gold nanorods are likely to retain a certain degree of their colloidal properties and are non-isotropically distributed before being bound to the surface of a silicon substrate.…”
Section: Resultsmentioning
confidence: 99%